Analisis Gangguan Hubung Singkat pada Generator Menggunakan Relay Arus Lebih di PT. Oki Pulp and Paper - As’ad Mubarok; M. Saleh Al Amin; Irine Kartika F; Yudi Irwansi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Generators are an important component in electrical generation. One of the disturbances that occurs in the generator is a short circuit fault. PT Oki Pulp and Paper has a Diesel Generator which is equipment that can be used as an alternative electrical generator to meet backup electricity needs, when a trip / shutdown occurs, the diesel generator will become backup power. The diesel generator observed is YCSR with a capacity of 3875 KVA/380 Volts. The purpose of this research is to analyse the Short Circuit Disturbance of Diesel Generator YCSR 3875 KVA and analyse the calculation of the time required for Over Current Protection on short circuit disturbance of Diesel Generator YCSR 3875 KVA. The research was conducted at the DG House of PT Oki Pulp and Paper in December 2024. The results of the short circuit fault analysis obtained are 17,042.40 A. The time required for the relay to disconnect the electricity during a short circuit is 4.09 seconds. The time obtained from the calculation is quite short, it can be seen that the short circuit fault that occurred was 17,042.40 A. To get the results of the relay working time, there is a calculation to find out how much TMS is determined through calculation, from the calculation getting the TMS result of 1,007 seconds. With TMS = 1.007 seconds, calculations are carried out to find the time required for the overcurrent relay to send a signal to the circuit breaker.